Photodithazine-mediated antimicrobial photodynamic therapy against fluconazole-resistant Candida albicans in vivo - Alves, Fernanda [UNESP] (2019)
This study evaluated the efficacy of antimicrobial Photodynamic Therapy (aPDT) against fluconazole-resistant Candida albicans in a murine model of oral candidosis. Mice were inoculated with two clinical isolates (R10, R15) and one reference strain (ATCC) of resistant C. albicans to produce oral candidosis. After inoculation, aPDT mediated by Photodithazine((R)) (PDZ) and LED light was performed. The use of PDZ or light only was also investigated. Additional animals were treated with Nystatin (NYS). Untreated or healthy mice were also evaluated. Microbiological evaluation was performed by recovering C. albicans from the tongue via colony-forming units. Animals were killed 24 hours after treatments, and the tongues were removed for histological analysis. Data were analyzed by one-way ANOVA and Tukey test (P < .05). The results demonstrated that all strains showed the same behavior after aPDT and NYS treatment. A significant reduction in C. albicans viability was achieved after both treatments for R15 and ATCC. No significant reduction was verified for C. albicans R10 submitted to aPDT or NYS. The histological analysis revealed that aPDT did not cause side effects on tissues. aPDT was effective for inactivation of two fluconazole-resistant C. albicans of the three strains evaluated.